(untitled) - Honova, Zuzana (Romanica Olomucensia, 2012)
The article deals with the matter of explicitation in legal texts. It begins by defining the term itself and then it treats of the causes leading to a larger extent of explicitation in legal texts. It sees them particularly in the efforts to express everything as precisely as possible and to compensate the insufficient equivalence of legal terms. In addition to that, the syntactic differences and the legal style itself are also the causes of explicitation.
Keywords: explicitation; implicitation; translation; legal language; legal style; legal text.